Are global mangrove carbon stocks driven by rainfall?. Issue 10 (15th October 2016) - Sanders, Christian J.; Maher, Damien T.; Tait, Douglas R.; Williams, Darren; Holloway, Ceylena; Sippo, James Z.; Santos, Isaac R.
Abstract: Mangrove forests produce significant amounts of organic carbon and maintain large carbon stocks in tidally inundated, anoxic soils. This work analyzes new and published data from 17 regions spanning a latitudinal gradient from 22°N to 38°S to assess some of the global drivers (temperature, tidal range, latitude, and rainfall) of mangrove carbon stocks. Mangrove forests from the tropics have larger carbon stocks (895 ± 90 t C ha −1 ) than the subtropics and temperate regions (547 ± 66 t C ha −1 ). A multiple regression model showed that 86% of the observed variability is associated with annual rainfall, which is the best predictor of mangrove ecosystem carbon stocks. Therefore, a predicted increase in rainfall along the tropical Indo‐Pacific may increase mangrove forest carbon stocks. However, there are other potentially important factors that may regulate organic matter diagenesis, such as nutrient availability and pore water salinity. Our predictive model shows that if mangrove deforestation is halted, global mangrove forest carbon stocks could increase by almost 10% by 2115 as a result of increased rainfall in the tropics. Key Points: Mangroves from subtropics to the temperate regions have carbon stocks of 547 ± 66 t C ha −1, nearly half of what is found in the tropics From variables used in this work (temperature, tidal range, latitude, and rainfall) rainfall is the best predictor of mangrove carbon stocks Increasing rainfall in the tropical Indo‐Pacific may increase global mangrove carbon stocks